An Examination of Lexical Bundles in Linguistics’ Published Research Articles of by Indonesian Writer - Ina Insani (International Journal of English Linguistics, Literature, and Education (IJELLE), 2022)
The analysis of lexical bundles have done by everal studies from various genres and registers. However, the majority of the studies of lexical bundles in academic discourses which wrote by Indonesia were only focused on the level of expertises and English proficiencies. Therefore, one of the linguistic features that could be a characteristic marker in academic writing which wrote by L2 English writers, including Indonesian, is through the identification of lexical bundes. In addition, to fill this need in revealing the characteristics of research articles which wrote by Indonesian writers, the present study identifies lexical bundles used in academic writing focusing on applied linguistics. By using corpus-based analysis, this study takes a wider analysis than previous work. Structural classification by Biber et al., (2004) and functional taxonomy approach by Hyland (2008a) were applied. The results reveal that 1) Indonesian writer has advanced writing in academic text because they use various structure of lexical bundles 2) the use of noun phrase category dominate the text 3) the verb phrase category was the second most highly used in the text. These results show that Indonesian writer was more varied in the way they express their logical view in their research articles, especially on applied linguistics.